Pregnancy and Congenital Heart Disease - Roos-Hesselink, Jolien W.; Johnson, Mark R. (Springer International Publishing : Imprint: Springer, 2017)
This book describes the risks facing patients with congenital heart disease who wish to become pregnant and the ways in which these patients can best be followed and treated during pregnancy. In addition, the organization of care around the delivery is discussed in detail. The first section provides clear advice on pre-pregnancy risk estimation, counseling of patients, medication use, and inheritance. The specific risks associated with congenital heart defects of differing severity are then explained, with guidance on monitoring and management. The coverage includes simple lesions such as atrial and ventricular septal defects, conditions associated with moderate risk, including tetralogy of Fallot and coarctation, and complex disease such as a Fontan or Mustard repair. The final section is devoted to delivery and considers the mode of delivery, anesthetic use, and postpartum care. Readers will find much information that is underreported in the literature, and the book goes well beyond the European Society of Cardiology guidelines, for example, by considering medical conditions not defined as high risk and addressing the organization of care thoroughly.
Keywords: Medicine.; Obstetrics.; Cardiology.; Cardiac surgery.; elektronické knihy; electronic books